2013
DOI: 10.1021/ol400294v
|View full text |Cite
|
Sign up to set email alerts
|

Atkamine: A New Pyrroloiminoquinone Scaffold from the Cold Water Aleutian Islands Latrunculia Sponge

Abstract: A new pyrroloiminoquinone alkaloid, named atkamine, with an unusual scaffold was discovered from a cold, deep water Alaskan sponge Latrunculia sp. collected from the Aleutian Islands. Olefin metathesis was utilized to determine the location of the double bond in the hydrocarbon chain. The absolute configuration was determined by using computational approaches combing with the ECD (electronic circular dichroism) spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
(37 reference statements)
0
30
0
Order By: Relevance
“…The ECD spectroscopy was first employed in the structural elucidation of discorhabdins by Grkovic et al in 2008 [9]. Since then, this technique has become particularly attractive and useful for confirming the absolute configuration of discorhabdins because of their conformationally rigid structures, strong UV absorption and circular dichroism properties [10,11,13,21]. So far, ECD spectroscopy is also one of the most effective techniques to secure the absolute configurations of discorhabdins-type alkaloids with a large number of stereogenic centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ECD spectroscopy was first employed in the structural elucidation of discorhabdins by Grkovic et al in 2008 [9]. Since then, this technique has become particularly attractive and useful for confirming the absolute configuration of discorhabdins because of their conformationally rigid structures, strong UV absorption and circular dichroism properties [10,11,13,21]. So far, ECD spectroscopy is also one of the most effective techniques to secure the absolute configurations of discorhabdins-type alkaloids with a large number of stereogenic centers.…”
Section: Discussionmentioning
confidence: 99%
“…So far, Latrunculia sponges represent one of the major reservoirs of pyrroloiminoquinone-type alkaloids. More than 40 pyrroloiminoquinone alkaloids belonging to the subclasses tsitsikammamines, makaluvamines, and discorhabdins have been reported from this genus, the discorhabdins being the largest and the most diverse [5,8,13,14]. Discorhabdins are a unique class of nitrogenous pigments possessing a characteristic tetracyclic pyrido [2,3-h]pyrrolo [4,3,2-de]quinoline core bound to a cyclohexanone substituent at the spiro center C-6 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Monanchocidin A was compared against all publicly available NCI-60 data using the CellMiner Database Version 1.4 (Reinhold et al, 2012). Utilizing the Compare (Zhou et al, 2000) algorithm and Pearson correlation coefficients, it was found that monanchocidin A shared a 0.638 Pearson correlation with ptilomycalin A (Figure 6). A Pearson correlation value above 0.6 is considered somewhat statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Growing interest in sulfur-containing heterocycles as anti-tumor agents emphasizes the need for new method development in this area. [12] To date, there is only a single report of a benzodihydrothiophene synthesis employing rhodium carbenes with acceptor-substituted diazo compounds. [13] The authors of this study hypothesize that the lack of development of this methodology is due to a propensity of the highly nucleophilic sulfur atom to attack the carbene directly to form an ylide.…”
mentioning
confidence: 99%